SEMANTIC ANALYSIS OF THE PAST CONTINOUS TENSE OF THE VERB IN THE UDMURT LANGUAGE - K.S. Efimov (Многоязычие в образовательном пространстве)
The article is devoted to the consideration of the semantics of the Past Continuous Tense of the Udmurt verb. One of the main functions of this form is to mark actions or events in the past that are characterised by the duration of the course and incompleteness. This Past Tense is used, as a rule, to describe permanent situations of the past, as well as the actions that occur simultaneously with others and serve as a background for them. The Past Continuous Tense in the Udmurt language has two variants, which are formed analytically. The first component in both cases is the semantic verb in the Present Tense. The second component is the auxiliary unchangeable verb val ‘was’, or vylem ‘was, it turns out’. In the second case, the semantics of indirect evidentiality is additionally realised, which indicates that the speaker was not a direct eyewitness of the event or action being described. In the first case, the form will be neutral in relation to the category of evidentiality. From the typological point of view, the first form can be attributed to the Indicative Mood (Indicative Imperfect), the second form should be attributed to the Non-Obvious Mood (Evidential Imperfect). The main research methods used were the continuous sampling method and the contextual analysis method. The descriptive method was used to present the research results. Based on the analysis, 4 temporal-semantic meanings expressed by the Past Continuous Tense forms of the Udmurt verb were identified: the meaning of a single continuous action in the past; the meaning of a background action; the meaning of a preceding action; the meaning of multiple actions in the past.